Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/582768
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Human Cytochrome P450 and ArylamineN-Acetyltransferase: Susceptibility to Head and Neck Cancers

Abstract: The occurrence of head and neck cancer (HNC) is associated with smoking and alcohol drinking. Tobacco smoking exposes smokers to a series of carcinogenic chemicals. Cytochrome P450 enzymes (CYP450s), such as CYP1A1, CYP1B1, and CYP2D6, usually metabolize carcinogens to their inactive derivatives, but they occasionally convert the chemicals to more potent carcinogens. In addition, via CYP450 (CYP2E1) oxidase, alcohol is metabolized to acetaldehyde, a highly toxic compound, which plays an important role in carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 168 publications
(262 reference statements)
1
35
0
Order By: Relevance
“…Thus, 55 publications were eligible. Then, 2 review articles, [ 19 20 ] 3 papers [ 2123 ] on precancerous lesions, and 1 study [24] on other polymorphic sites of CYP2E1 rather than RsaI/PstI were discarded. Next, 2 studies [ 25 26 ] lacking of controls and 4 studies [ 2730 ] providing insufficient data were also eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 55 publications were eligible. Then, 2 review articles, [ 19 20 ] 3 papers [ 2123 ] on precancerous lesions, and 1 study [24] on other polymorphic sites of CYP2E1 rather than RsaI/PstI were discarded. Next, 2 studies [ 25 26 ] lacking of controls and 4 studies [ 2730 ] providing insufficient data were also eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, when acute myocardial infarction patients were treated with metoprolol (a substrate for CYP2D6) and co-treated with paroxetine (an inhibitor of CYP2D6), paroxetine inhibited the metabolism of metoprolol and increased its concentration maximum (Cmax), resulting in enhanced therapeutic effects and/or adverse effects, such as severe dizziness, fainting and heart failure [34]. In anti-cancer therapy, many studies have demonstrated that altered expression of DMEs can influence the sensitivity and toxicity of drugs in target cells, and the expression of DMEs plays a pivotal role in chemotherapy sensitivity, resistance, and/or carcinogenesis [35,36]. The enzyme activity of CYP2D6 significantly impacts the anti-estrogen effect of tamoxifen in cancer therapy, because it is the most important CYP in the conversion of tamoxifen to 4-OH tamoxifen [37].…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, AhR migrates to the nucleus to regulate the expression of genes, such as CYP1A1, which is a member of the cytochrome P450 superfamily of enzymes . CYP1A1 has an essential role in the metabolism of drugs and chemicals, and polymorphisms in this gene have been associated with different tumors …”
Section: Immunomodulatory Features Of Ido Activitymentioning
confidence: 99%